A population level analysis of mental health and non-communicable disease (NCD) in the Philippines using predictive modelling analysis - R. Samonte, Francis Gregory; Guzman, Ma. Teresa De; Gonzales, Rolando (International Journal of Psychosocial Rehabilitation, 2020)
The epidemic brought about by non-communicable diseases (NCD) and the lack of adequate data on the state of mental health (MH) in the Philippines have converged that threatens to overwhelm the health care infrastructure. Population level analysis is severely lacking that could otherwise provide a fundamental basis for critical analysis needed to address health policy interventions. The use of mathematical algorithm as a form of mixed- method analysis in population level studies in developing countries has the potential to elucidate associations between diseases. Our study looks into the Philippine national data on mental health and NCD from 2002-2016 to determine the association and predictive correlation between mental health and NCD using predictive modeling study; designed to expand current understanding on the developmental origins and trajectories of these diseases from a developing country perspective